2013
DOI: 10.1111/pre.12006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on growth and physiology of Ulva lactuca (Chlorophyta) in a rockpool‐scenario

Abstract: Rising atmospheric CO2-concentrations will have severe consequences for a variety of biological processes. We investigated the responses of the green alga Ulva lactuca (Linnaeus) to rising CO2-concentrations in a rockpool scenario. U. lactuca was cultured under aeration with air containing either preindustrial pCO2 (280 matm) or the pCO2 predicted by the end of the 21st century (700 matm) for 31 days. We addressed the following question: Will elevated CO2-concentrations affect photosynthesis (net photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 38 publications
(110 reference statements)
3
44
0
Order By: Relevance
“…However, the role of CO 2 is debatable with some studies showing that F v /F m is not affected by elevated CO 2 levels (Hofmann et al 2012;Olischläger et al 2013;Kram et al 2016) and others indicating that chlorophyll fluorescence increases under high CO 2 concentrations . We found here that the photosynthetic efficiency of G. lemaneiformis was more strongly affected by greater NH 4 + concentrations than by higher CO 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of CO 2 is debatable with some studies showing that F v /F m is not affected by elevated CO 2 levels (Hofmann et al 2012;Olischläger et al 2013;Kram et al 2016) and others indicating that chlorophyll fluorescence increases under high CO 2 concentrations . We found here that the photosynthetic efficiency of G. lemaneiformis was more strongly affected by greater NH 4 + concentrations than by higher CO 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not found in algal cells stressed by Na 2 CO 3 , due to the high pH and Na + toxic effects. High pH can reduce algal photosynthetic ability and pigment content, because the dissolved CO 2 in water is limited (Axelsson et al 1999;Olischläger et al 2013). Meanwhile, the depletion of dissolved CO 2 stimulates ROS formation (Sültemeyer et al 1993).…”
Section: mentioning
confidence: 99%
“…In algae, lower dose of NaHCO 3 can promote the photosynthesis as HCO − 3 is the carbon source (Bhatti & Colman 2011;Huege et al 2011), but higher dose of NaHCO 3 and Na 2 CO 3 is harmful due to the high pH and Na + toxic effects. It has been reported that high pH reduces algal photosynthetic ability and pigment content, because it limits dissolved CO 2 -concentration in water (Axelsson et al 1999;Olischläger et al 2013). The depletion of dissolved Effects of NaCl and Na2CO3 stresses 1315 CO 2 can stimulate ROS formation, increase antioxidant enzyme activity (Sültemeyer et al 1993) and even induce PCD (Vardi et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the negative effects of increased CO2 on calcifying organisms, previous studies have shown that some photosynthetic organisms, such as seagrasses (Koch et al, 2013;Palacios and Zimmerman, 2007), phytoplankton (Fu et al, 2012;Hattenrath-Lehmann et al, 2015), and macroalgae (Olischläger et al, 2013;Young and Gobler, 2016) may benefit from a high CO2 environment. Such photosynthetic autotrophs may also have the capacity to buffer carbonate chemistry, 15 potentially alleviating the harmful effects of excessive CO2 on calcifying organisms.…”
Section: Introduction 25mentioning
confidence: 88%
“…While future increases in CO2 may promote the growth of fast-growing, macroalgae such as Ulva (Björk et al, 1993;Olischläger et al, 2013;Gobler, 2016, 2017) and could, in turn, could provide chemical resilience for calcifying organisms in acidified environments (Anthony et al, 2013;Wahl et al, 2017), such interactions have yet to be fully explored.…”
Section: Introduction 25mentioning
confidence: 99%